Arbuscular Mycorrhizal Fungi Alleviate Drought Stress in C3 (Leymus chinensis) and C4 (Hemarthria altissima) Grasses via Altering Antioxidant Enzyme Activities and Photosynthesis - Li, Junqin; Meng, Bo; Chai, Hua; Yang, Xuechen; Song, Wenzheng; Li, Shuixiu; Lu, Ao; Zhang, Tao; Sun, Wei (Frontiers in Plant Science, 2019)
Abstract As one of the most important limiting factors of grassland productivity, drought is predicted to increase in intensity and frequency. Greenhouse studies suggest that arbuscular mycorrhizal fungi (AMF) can improve plant drought resistance. However, whether AMF can improve plant drought resistance in field conditions and whether the effects of AMF on drought resistance differ among plants with different photosynthetic pathways remain unclear. To evaluate the effect of indigenous AMF on plant drought resistance, an in situ rainfall exclusion experiment was conducted in a temperate meadow in northeast China. The results showed that AMF significantly reduced the negative effects of drought on plant growth. On average, AMF enhanced plant biomass, photosynthetic rate (A), stomatal conductance (gs), intrinsic water use efficiency (iWUE) and superoxide dismutase (SOD) activity of the C3 species Leymus chinensis by 58%, 63%, 38%, 15% and 45%, respectively, reduced levels of malondialdehyde (MDA) by 32% under light and moderate drought (rainfall exclusion of 30% and 50%, respectively). However, under extreme drought (rainfall exclusion of 70%), AMF elevated only aboveground biomass and catalase (CAT) activities. Averagely, AMF increased the aboveground biomass, A and CAT activity of Hemarthria altissima (C4) by 37%, 28% and 30%, respectively, under light and moderate droughts. The contribution of AMF to plant drought resistance was higher for the C3 species than that for the C4 species under both light and moderate drought conditions. The results highlight potential photosynthetic type differences in the magnitude of AMF associated enhancement in plant drought resistance. Therefore, AMF may determine plant community structure under future climate change scenarios by affecting the drought resistance of different plant functional groups.